Hole-conducting self-assembled monolayers for perovskite solar cells
By using the pore material synthesized by the phosphoric functionalized carbazoleidine derivative V1036, a self-assembled single layer (SAM) is formed, which solves the problem of difficult to achieve uniformity and thinness of the HTM layer, reduces material consumption and avoids multiple doping processes, and improves the efficiency and stability of the photovoltaic cell.
Patent Information
- Application Number
- JP2020560151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-06-26
- Filing Date
- 2019-04-25
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2039-04-25
AI Technical Summary
When preparing efficient photovoltaic cells, it is difficult for the prior art to achieve uniformity and thinness of the HTM layer, and there are problems of material waste and multiple doping processes, especially in large-scale production.
A new pore material V1036 is used, which is synthesized by phosphate functionalized carbazolidine derivatives, with good self-assembly capability and adaptability to structural surfaces, and can form efficient self-assembly single layer (SAM), reducing material consumption and avoiding multiple dopings.
The uniformity and thinness of the HTM layer are achieved, material consumption is reduced, multiple doping processes are avoided, the efficiency and stability of photovoltaic cells are improved, and it is suitable for large-scale production.
Smart Images

Figure 0007663191000047 
Figure 0007663191000048 
Figure 0007663191000049
Abstract
Description
[Technical field]
[0001] Solar cells with hybrid perovskite absorber layers have surpassed the 20% power conversion efficiency (PCE) limit in a surprisingly short time, achieving a record efficiency of 22.7% (see "NREL efficiency chart" https: / / www.nrel.gov / pv / assets / images / efficiency-chart.png, 2017). Published results for perovskite solar cells (PSCs) (WS Yang et al., Science 2017, 356, 1376-1379) were obtained in a nip configuration (often referred to in the literature as "regular" PSCs) with TiO2 (compact, mesoporous layer) as the electronic conductor on a transparent conducting oxide (TCO) substrate. In the pin configuration, where a hole transport material (HTM) is first deposited on the TCO (often referred to in the literature as "inverted" PSCs), efficiencies of over 20% have also been reported (J. Zhao et al., Energy Environ. Sci. 2016, 9, 3650-3656, and M. Stolterfoht et al., Sci. 2017, 10, 1530-1539), making them competitive products. All these results stimulate more research in this rapidly developing field. [Background technology]
[0002] pin PSCs have several advantages over the more common nip architecture. First, they avoid the high temperature annealing required for the formation of TiO2. Second, they are known to have a much lower pronounced hysteresis, even if hysteresis can still be detected under certain conditions, resulting in essentially "hysteresis-free" devices (JH Heo et al., Energy Environ. Sci. 2015, 8, 1602-1608) (D. Bryant et al., J. Phys. Chem. Lett. 2015, 6, 3190-3194 and P. Calado, Nat. Commun. 2016, 7, 13831). Third, instead of gold, the much cheaper copper can be used as the metal contact layer (J. Zhao et al., J. Huang, Energy Environ. Sci. 2016, 9, 3650-3656). Secondly, doping of the charge selective contacts is not required, improving long-term stability, as dopants in spiro-OMeTAD (2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)9,9′-spirobifluorene) are known to reduce stability. Finally, the pin configuration, resulting from lower parasitic absorption in the front contact (KABush et al., 23.6% efficient monolithic perovskite / silicon tandem solar cells with improved stability, Nature energy Vol.2,2017,17009_1-7), has been shown to enable higher tandem efficiency potential and thus have great potential for further development.
[0003] In a recent paper (Stolterfoht et al., Energy Environ Sci. 2017, 10(6), 1530) it was shown that a decrease in the thickness of the HTM layer leads to an increase in the filling factor (FF). However, as the film gets thinner, the open circuit voltage (Voc) drops sharply. This is due to a possible incomplete coverage of the indium tin oxide (ITO), resulting in direct contact between the perovskite and the ITO.
[0004] Recently, there have been some studies by Y. Hou et al. on the use of phosphonic acid-based mixed C60 / organic self-assembled monolayers (SAMs) as electronic conductors in nip-PSCs instead of TiO2 (Y. Hou et al., Adv. Mater. Interfaces 2017, 4, 1700007, and Y. Hou et al., Science 2017, 358, 1192-1197). Similarly, siloxane-functionalized C60 SAMs were also used by P. Topolovsek et al. (J. Mater. Chem. A 2017, 5, 11882-11893). [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] "NREL Efficiency Chart," https: / / www.nrel.gov / pv / assets / images / efficiency-chart.png, 2017. [Non-Patent Document 2] WSYang et al., Science 2017, 356, 1376-1379 [Non-Patent Document 3] J. Zhao et al., Energy Environ. Sci. 2016, 9, 3650-3656, and M. Stolterfoht et al., Sci. 2017, 10, 1530-1539 [Non-Patent Document 4] JHHeo et al., Energy Environ.Sci.2015,8,1602~1608 [Non-Patent Document 5] D. Bryant et al., J.Phys.Chem.Lett.2015,6,3190-3194 and P.Calado, Nat.Commun.2016,7,13831 [Non-Patent Document 6] J. Zhao et al., J. Huang, Energy Environ, Sci.2016, 9, 3650~3656 [Non-Patent Document 7] KABush et al., 23.6% efficient monolithic perovskite / silicon tandem solar cells with improved stability, Nature energy Vol.2,2017,17009_1-7 [Non-Patent Document 8] Stolterfoht et al., Energy Environ Sci. 2017, 10(6), 1530 [Non-Patent Document 9] Y. Hou et al., Adv. Mater. Interfaces 2017, 4, 1700007, and Y. Hou et al., Science 2017, 358, 1192-1197 [Non-Patent Document 10] P.Topolovsek et al., J.Mater.Chem.A 2017,5,11882-11893 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention relates to uniformly shaped layers on TCOs with minimal thickness that are hole transported due to hole conducting materials that are configured for self-assembly on the corresponding surface. Furthermore, minimizing parasitic absorption, reducing material consumption and avoiding doping procedures are problems to be solved, especially in relation to providing a scalable technology. [Means for solving the problem]
[0007] Furthermore, the present invention aims to provide an HTM that is relatively resistant to perovskite processing and can conformally overlay any structured surface, such as structured silicon with pyramids of a few microns in height that have been processed by wet chemical etching, as is common in solar cells. [Brief description of the drawings]
[0008] [Figure 1]Synthesis of phosphonic acid functionalized carbazole derivative V1036: a) 1,2-dibromoethane (6.5 ml / eq.), TBABr (0.3 eq.), 50% aq. KOH (15 equiv.), 72 h, 60 °C; b) triethyl phosphite (3.6 ml / eq.), 18 h, 165 °C; c) 4,4′-dimethoxydiphenylamine (3 equiv.), Pd(OAc) (0.3 equiv.), P(t-Bu)-BF (0.6 equiv.), NaOt-Bu (3 equiv.), anhydrous toluene (24.5 ml / eq.), Ar, 5 h, reflux; d) (10 equiv.), anhydrous dioxane (29.4 ml / eq.), Ar, 24 h, 25 °C; e) MeOH (19.6 ml / eq.), HO (19.6 ml / eq.), 15 h, rt. [Diagram 2] A) UV / VIS absorption spectra of a 10-4 M THF solution of V1036 and PTAA (polytriarylamine); B) UV / VIS absorption spectra of bare ITO substrate, ITO with PTAA, and ITO with a SAM of 100% V1036. [Diagram 3] TGA heating curve of V1036. Heating rate 10℃ min-1. [Figure 4] A) FTIR absorption spectra of monolayers on Si / ITO substrates prepared from (a) a 1 mM solution of V1036, (b) a 1 mM mixed solution of V1036:C4 (1:9), and (c) a 1 mM solution of C4. B) FTIR spectrum of the major mass of V1036 in a KBr pellet. [Diagram 5] A) FTIR absorption spectra in the spectroscopic range 1150–1300 cm-1 and B) 1400–1600 cm-1 of monolayers on Si / ITO substrates prepared from (a) a 1 mM solution of V1036, (b) a 1 mM mixed solution of V1036:C4 (1:9), and (c) a 1 mM solution of C4. [Figure 6] A) Contact angle depending on the percentage of V1036 in the SAM composition; B) Equilibrium contact angle of perovskite solution on a SAM of 100% C4; PTAA; 100% V1036. [Figure 7] JV characteristics of the strongest PSCs with HTMs of PTAA and SAM. [Figure 8]A: JV characteristics of forward and reverse scans of the most powerful PSC with HTM of SAM of PTAA and 10% V1036 90% C4. B: EQE and integrated Jsc of the most powerful PSC with SA-HTM of PTAA and 10% V1036 90% C4. Insertion shows the statistical distribution of Jsc. [Figure 9] SEM top and cross-sectional views of PTAA and 10% V1036 90% C4. [Figure 10] Comparison of the properties of the “triple cation” perovskite absorber (Cs5(MA17FA83Pb(I83Br17)3)95) applied to different HTM-SAMs, V1036, PTAA, V1193 and V1194. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Thus, one aspect of the present invention comprises providing a compound that functions as an HTM and comprises at least one molecule of formula (I): [ka] wherein L is a linking fragment, A is an anchor group, and HTF is a hole transport fragment selected from formula II or III: Polycyclic ZDZ, (II) where Z and D are heterocyclic or at least one of Z or D contains a heteroatom selected from the group N, S, O, Si, Z is a C5 or C6 substituted or unsubstituted aromatic group, D is N or a C5 or C6 aromatic group, and two carbon atoms of the aromatic group D are each bonded to one of the two aromatic groups Z to form a tricycloundecane, tricyclotetradecane or tricyclotetradecane derivative; or [ka] In the formula, R is a substituent.
[0010] Due to the localization of electrons, the compound according to the present invention functions as a hole-conducting material. For this purpose, compounds that allow electron localization throughout the system are preferred. In particular, delocalization between the Z fragments via the fragment D is preferred. Thus, D is preferably an aromatic fragment and / or an element with electron-pushing properties, and is connected to the fragment Z. In particular, compounds that have a symmetric structure, i.e., can be mirrored along an axis, are preferred. Mirroring refers to a schematic structure and not necessarily to an actual three-dimensional appearance.
[0011] It is advantageous to have the mirror axis pass through component D so that the two Z components are equal or opposite.
[0012] To form a SAM, the molecules of formula (I) can be mixed with other molecules called "filler molecules" (FMs). FMs are generally molecules or mixtures of molecules formed by an anchor group (e.g. phosphonic acid, phosphoric acid, sulfuric acid, sulfonic acid, carboxylic acid, siloxane) capable of binding to the surface of the TCO, an alkyl chain containing N carbon atoms (N=1-18), and functional methyl, halogen, amino, bromide, ammonium and / or sulfur groups. Examples include ethyl or butyl phosphonic acid ("C2" or "C4") or (aminomethyl) phosphonic acid. FMs act as passivating agents to reduce charge carrier recombination between the TCO and the perovskite, and as agents to modify the wettability of the TCO. However, preparations without FMs are usually possible with selected proportions of HTF, L and A, and also without disadvantages.
[0013] The proportion x of the HTM in the mixture ranges from 0.02 to 1. The proportion of filler molecules (FM) is given by y=(1-x). In the HTM of formula (I), n is preferably equal to 1 or 2.
[0014] In a preferred embodiment of the invention, D is a C5 or C6 heteroaromatic group, the heteroatoms being N, Si, S and / or O.
[0015] In a further preferred embodiment, the hole conducting fragment (HTF) is selected from one of those given in formulas IV to XIX. [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] or [ka]
[0016] Alternatively or additionally, the R groups are independently H; 10 Alkyl; C2-C 10 Alkenyl; C3~C 20 Selected from the group consisting of cycloalkyl; C3-C8 heterocycloalkyl, alkoxy, aryloxy, alkylthio, arylthio, amino, amide, ester, carboxylic acid, dialkoxydiphenylamine, carbamate, urea, ketone, aldehyde, cyano, nitro, halogen; (cycloalkyl)alkyl; and (heterocycloalkyl)alkyl.
[0017] In particular, the R groups are independently selected from hydrogen; [ka] [ka] During the ceremony, The dotted line represents the bond connecting R to the HTF of formula II or III; X represents halogen (F, Cl, Br, I); R''' represents hydrogen, alkyl (C1-C 12 ) and / or R″ represents hydrogen, alkyl, alkoxy (—CH3; —OCH3).
[0018] In a further embodiment, the linking fragment L is C1-C9 alkylene, C4-C 20 Arylene, C4~C 20 Heteroarylene, C4-C 20 Alkyl arylene, C4-C 20 heteroalkylarylene, the heteroatom being selected from O, N, S, Se, Si, said alkylene, arylene, heteroarylene, alkylarylene, heteroalkylarylene, heteroalkylarylene, if they consist of three or more carbon atoms, may be linear, branched or cyclic, in particular selected from any one of the following: [ka] During the ceremony, The dotted line represents the bond where L is linked to an HTF according to formula II or III.
[0019] In a preferred embodiment, the anchor group A (head group) is selected from phosphonic acid, phosphoric acid, sulfate, sulfonic acid, carboxylic acid, siloxane, in particular any one of the following: [ka] wherein the dotted line represents the bond connecting A to L, and R' is preferably aliphatic, according to any one of the preceding claims.
[0020] A further aspect of the present invention is to provide a hole conducting material which constitutes a step of the present invention.
[0021] Another aspect of the invention relates to an opto-electrical and / or optoelectronic component, which comprises the inventive steps in combination according to one of the preceding embodiments.
[0022] In particular, the optoelectrical and / or optoelectronic component comprises a hole conducting material, the hole conducting material comprising a compound of Formula II or III.
[0023] Preferably, the photoelectric and / or photoelectrochemical device is a solid-state photovoltaic device which is a solid-state solar cell comprising an organic-inorganic perovskite as sensitizer molecule in the form of at least one monolayer.
[0024] The term "perovskite" as used herein means "perovskite structure" and does not specifically refer to the perovskite material CaTiO3. For purposes of this specification, "perovskite" includes any material, preferably any material having the same type of crystal structure as calcium titanium oxide, and in which a divalent cation is replaced by two separate monovalent cations. Perovskite structures have a general stoichiometry AMX3, where "A" and "M" are cations and "X" is an anion. The "A" and "M" cations can have different charges, and in the original perovskite mineral (CaTiO3), the A cations are divalent and the M cations are tetravalent. For purposes of this invention, the formula for a perovskite consists of a structure having metal atoms carrying one (1), two (2), three (3) or four (4) cations, which may be the same or different, and / or one or two (2) anions and / or two or three positive charges, according to formulae given elsewhere herein.
[0025] Furthermore, the organic-inorganic perovskite layer material of the optoelectronic and / or optoelectrochemical device preferably has a perovskite structure of any one of the following formulae: A1 A 2 A 3 A 4 MX 3、 A 1 A 2 A 3 MX3, A 1 A 2 MX4;A 1 MX3;A 1 A 2 N 2 / 3 X4;A 1 N 2 / 3 X3;BN 2 / 3 X4;A 1 2NMX6;BMX4, during the ceremony, - A 1 , A 2 , A 3 , A 4 is independently either an organic monovalent cation or mixtures thereof selected from primary, secondary, tertiary or quaternary organic ammonium compounds, including N-containing heterocycles and ring systems, where A and A' have independently from 1 to 60 carbon atoms and from 1 to 20 heteroatoms (e.g., methylammonium or formamidinium) or inorganic cations (e.g., Na, K, Rb, Cs). - B is an organic divalent cation selected from primary, secondary, tertiary or quaternary organic ammonium compounds having 1 to 60 carbon atoms, 2 to 20 heteroatoms and having two positively charged nitrogen atoms; - M is Cu 2+ , Ni 2+ , Co 2+ , Fe 2+ , Mn 2+ , Cr 2+ , Pd 2+ , Cd 2+ , Ge 2+ , Sn 2+ , Pb 2+ ,EU 2+ or Yb 2+ is a divalent metal cation selected from the group consisting of: - N, Bi 3+ and Sb 3+ selected from the group consisting of: - X is independently Cl -, Br - , I - , N.C.S. - , C.N. - and N.C.O. - X may also be a mixture of the halides / anions listed.
[0026] In a preferred embodiment, the compound according to the invention for forming a SAM is characterized as follows: the moiety x of formula I is x=1, which results in the moiety y of the FM (filler molecule) being y=0; the anchor group A is formed from a phosphonic acid group and L is C2; the hole-conducting fragment HTF is selected from formula (II) (ZDZ) where D is N and Z is a C6 cyclic aromatic group substituted with a methoxy group; in another preferred embodiment, as above, but Z is not substituted with a methoxy group. Both versions have in particular in common that they can be prepared without the use of a filler molecule (FM), without compromising their properties and stability.
[0027] A further aspect of the present invention is the use of the process of the present invention as a hole conducting material in opto-electrical and / or opto-electronic devices.
[0028] Formation of the compounds of the invention as SAMs on TCOs for use in inverted architecture perovskite solar cells can be achieved by two methods, one of which comprises the following steps:
[0029] First, a substrate coated with an oxide layer, preferably a TCO, is provided, which is immersed in a solution comprising a solvent and a compound according to the following formula: [ka] wherein L is a linking fragment, A is an anchor group, and HTF is a hole conducting fragment selected from formula II or III: Polycyclic ZDZ, (II), where Z and D are heterocyclic or at least one of Z or D contains a heteroatom selected from the group N, S, O, Si, Z is a C5 or C6 substituted or unsubstituted aromatic group, D is N or a C5 or C6 aromatic group, and the two carbon atoms of the aromatic group D are each bonded to one of the two aromatic groups Z to form a tricycloundecane, tricyclotetradecane or tricyclotetradecane derivative; or [ka] where R is a substituent; FMs are generally molecules or mixtures of anchor groups (e.g. phosphonic acid, phosphoric acid, sulfuric acid, sulfonic acid, carboxylic acid, siloxane) capable of binding to the surface of the TCO, alkyl chains with N carbon atoms (N=1-18), and functional methyl, halogen, amino, bromide, ammonium and / or sulfur groups, where x ranges from 0.02 to 1 and y is equal to (1-x). Examples of FMs include ethyl or butyl phosphonic acid ("C2" or "C4") or (aminomethyl) phosphonic acid. As a solvent for the solution, any liquid can be selected that is capable of dissolving the compound and ensuring immersion of the surface. The concentration of the compound in the solution is preferably in the range of 0.01 to 100 mM per liter. The time for immersing the surface to form the SAM is preferably at least sufficient for the molecules to bind to the oxide surface, preferably in the range of 5 minutes to 50 hours. After immersion, the substrate is removed from the solvent. In a preferred embodiment, the substrate is then thermally heated and / or cleaned.
[0030] In an alternative method, a compound according to the invention is spin-coated (e.g., spun) in solution with or without a FM. The optimal method for a selected HTM and potential substrate can be determined empirically, if necessary. EXAMPLES
[0031] Dimethoxydiphenylamine-substituted carbazole (V1036) functionalized with phosphonic acid was synthesized. The dimethoxydiphenylamine-substituted carbazole fragment can be found in several efficient HTMs for conventional perovskite solar cells, and the active hydrogen at the 9-position of the carbazole can be further utilized for functionalization with phosphonic acid anchor groups (head groups).
[0032] The synthesis was carried out in a four-step synthetic procedure starting from commercially available materials (see Figure 1). In the first step, 3,6-dibromocarbazole was alkylated with 1,2-dibromoethane to form intermediate compound 1. In the next step, this aliphatic bromide was converted to the phosphonic acid ethyl ester 2 via an Arbuzov reaction. Further, a palladium-catalyzed Buchwald-Hartwig amination reaction was used to introduce the dimethoxydiphenylamine fragment to give compound 3. Finally, the ester was cleaved with bromotrimethylsilane to give the phosphonic acid V1036. The structures of the synthesized compounds are shown in Table 1. 1 H- and 13 The product was confirmed by C-NMR spectroscopy. A more detailed description of the method of synthesis is provided below.
[0033] In an inverted PSC, the light first passes through the HTM layer, so it is important to minimize the parasitic absorption in this layer. -4 M was investigated by UV / VIS spectroscopy in a THF (tetrahydrofuran) solution (Figure 2A). The λ characteristic of the dimethoxydiphenylamine 3,6-substituted carbazole chromophore system was max =304nm strong π-π * Absorption bands and weak n-π bands from 350 to 450 nm * Compared to PTAA, V1036 has a broader absorption band, but the monolayer thickness is much smaller, making the absorption negligible when formed on ITO (Figure 2B).
[0034] As can be seen from FIG. 3, the V1036 substrate, which does not contain FM, is heated to 343°C (T dec) exhibited a 95% weight reduction, making it suitable for practical use in optoelectronic components.
[0035] To confirm the formation of a SAM on the ITO surface, FTIR (Fourier transform infrared spectroscopy) spectra of the self-assembled monolayer on the Si / ITO substrate were generated (Figure 4A) and compared with the spectrum of a V1036-based compound dispersed in a KBr tablet (Figure 4B). The spectrum of the SAM prepared from a 1 mM V1036 solution in methanol (100% V1036) exhibited peaks at 1238 and 1503 cm. -1 Two strong bands at 1442, 1461 and 1485 cm -1 The spectra are shown together with the lower intensity component near 1503 cm (Figure 4A, (a)). All the features observed in the spectrum of the monolayer are close to the absorption bands visible in the infrared spectra of V1036-based compounds, confirming the presence of V1036 on the surface of the ITO substrate. -1 The most intense band in is related to the C=C in the plane of the valence vibration of the aromatic ring of the carbazole structure and partly to the contribution of the C=C in the plane of the valence vibration of the p-methoxyphenyl group. The valence vibration of the C-N bond is at 1238 cm -1 These can be seen as strong bands around 1438~1442 and 1461~1466 cm -1 The two medium intensity bands nearby contain the symmetric and asymmetric CH3 deformation vibrations of a high proportion of methoxy groups. -1 The integrated absorbance intensity of the nearby band was measured to be reduced to 0.62 for a SAM prepared from a methanol solution with 0.1 mM V1036 and 0.9 mM C4 as FM (10% V1036 90% C4), indicating a reduced surface coverage by the V1036 compound compared to a SAM with 100% V1036 (relative intensity 1.00). Clearly, the reduction in surface coverage of the V1036 compound was not as high as would be expected from the composition of the absorbent solution, indicating a higher surface affinity of V1036 compared to C4.
[0036] In Figure 5, vibrational sum frequency generation (VSFG) spectra of SAMs of HTM (V1036 with and without filler molecules) on Si / ITO substrates are shown in the range of 1150–1300 cm -1 (A) and 1400-1600 cm -1 In the spectrum of the 100% V1036 SAM, the peak at about 1237 cm -1 (FIG. 5A, (a)) and about 1490 cm -1 Two peaks were identified in the FTIR spectrum of the same monolayer (Fig. 5B, (a)). These two bands correspond to the two most intense vibrational bands seen in the FTIR spectrum of the same monolayer (Fig. 5A, (a)). The Si / ITO substrate provides a substantial non-resonant SFG signal, which, as can be seen from equation (S1), interferes with the resonant signal, causing distortion of the spectrum. Due to this interference, a peak at approximately 1490 cm -1 The shape of the resonance centered at is similar to an asymmetric Fano type resonance, and in the FTIR spectrum (approximately 1503 cm -1 ) appears to be shifted in frequency.
[0037] No vibrational bands were identified in the spectrum of the 10% V1036 90% C4 SAM. The expected VSFG intensity should be about 100 times less than that of the 100% V1036 SAM. In such a case, the LSFG signal would be below the detection limit. However, the FTIR spectrum showed that the surface coverage of V1036 in the mixed SAM, about 0.62, corresponds to that of the pure V1036 SAM. The VSFG signal of the monolayer with such a surface coverage should still be detectable, but no signal was recorded. This measured VSFG signal is proportional to the asymmetry in the orientation of the investigated molecules and accordingly provides unique information about the molecular order of the surface. This indicates that the monolayer prepared from the mixed solution leads to a more disordered structure compared to the monolayer prepared from the pure V1036 solution.
[0038] To investigate the effect of SAMs on the surface energy and the effect of changing the proportion of mixed SAMs, contact angle measurements were performed using triple cation perovskite solutions as test liquids. As shown in Figure 6 / Table 1, the contact angles of PTAA, 100% V1036 SAM, and 100% C4 SAM are 42.6°, 26.3°, and 60.5°, respectively. The contact angle gradually changes for the mixed SAMs, confirming the presence of two species on the ITO surface. The difference in contact angle correlates with the polarity of the materials, with the non-polar aliphatic 100% C4 SAM giving higher angle values and the lowest value for the 100% V1036 SAM with functional methoxy groups.
[0039] [Table 1]
[0040] Good tuning of the energy levels is an important prerequisite for the efficient operation of the components. To investigate the effect of the SAM on the energy levels of the ITO substrate and to study the mass properties of V1036, the ionization potential (I p ) were measured (Table 2).
[0041] For the PTAA film spin-coated with 2 mg / ml toluene on ITO, the I p The I value obtained is close to the previously reported value of 5.16 eV. The substrate V1036 has an I of 5.04 eV. p For a 100% V1036 SAM formed on ITO, a value of 4.98 eV was obtained, which is in good agreement with the value for the substrate. A mixed SAM with a composition of 10% V1036 and 90% C4 showed a value of 5.09 eV. The mixed SAM showed a slightly higher I p values are given, it can be assumed that the changes are in the range of 0.1 eV and accordingly should not significantly affect the device performance.
[0042] [Table 2]
[0043] To investigate whether the formed SAM can function as an HTM, we used ITO / HTM / perovskite / C 60 We constructed pin-PSC devices with a Cu / BCP / Cu architecture (BCP: Bathocuproin). All devices used triple cation perovskites, with a thin layer of PTAA without dopant as a control HTM.
[0044] First, we investigated the effect of the ratio of V1036 to butylphosphonic acid (C4) on the device performance. As can be seen in Figure 7, the SAM with 10% V1036 achieved the highest result, a PCE of 17.8%. The control device with PTAA showed a slightly higher efficiency with a PCE of 18.4%.
[0045] To get a better insight into the variation of the different parameters, the statistical data are presented in Table 3. As can be seen, Jsc changes slightly and on average the HTM of the SAM is very close or even slightly better than that of the PTAA. This can be explained by the lower parasitic absorption by the HTM layer of the SAM. The average FF of the SAM is slightly lower than that of the PTAA (76.3%), reaching a maximum of 71.2% for the SAM with 25% V1036 and 75% C4, the best values being very close to the value of PTAA. At higher levels of V1036, a decrease in Voc was observed, possibly due to the direct contact between the perovskite and ITO. This assumption is supported by the fact that the devices without HTM with bare ITO showed a very poor performance, mainly due to a strong decrease in Voc.
[0046] Table 3. Average PSC performance parameters extracted from J / V scans, including (in brackets) the performance parameters and standard errors for the best devices. Statistics are based on 9–20 cells on different substrates with different HTMs.
[0047] [Table 3]
[0048] It is known that negligible hysteresis is observed in pin-PSCs. In the case of SAM-HTM, the best device with a SAM of 10% V1036 90% C4 showed only slightly stronger hysteresis than the control device with PTAA (Figure 8A).
[0049] To investigate the effect of the length of the aliphatic phosphonic acid as a filler molecule on the overall performance of the device, ethylphosphonic acid (C2) and n-hexylphosphonic acid (C6) were then tested. In the SAM of 10% V1036 90% C6, the perovskite film could hardly be formed due to poor wettability. The device using the filler of C2 showed a slight decrease in performance due to the decrease in Voc and Jsc. Therefore, C4 is one of the preferred lengths of the filler molecule in combination with V1036.
[0050] To further characterize the best devices, external quantum efficiency (EQE) measurements were performed. From Figure 8B, it can be seen that due to the very small thickness of the SAM, a small gain in current flow can be achieved. This is due to the reduced absorption of the HTM, as previously shown by UV / VIS absorption measurements (Figure 2). The Jsc values obtained by integrating the EQE data are in close agreement with those obtained from the J / V scan.
[0051] To determine whether the SAMs caused any difference in the morphology of the perovskite, scanning electron microscopy (SEM) studies were performed. As can be seen from the top and cross-sectional images in the SEM (Figure 9), the SAMs did not cause much change in the morphology of the perovskite, and the grains were similar to those of the control component.
[0052] Further information on methods of synthesis and characterization Chemicals were sourced from Sigma-Aldrich and TCI Europe and were used as received without further cleaning. 1 H and 13 C NMR spectra were recorded at room temperature on a Bruker Avance III (400 MHz) spectrometer. All data are given as chemical shifts in ppm. The course of reaction products was monitored by TLC on ALUGRAM SIL G / UV254 plates and developed using UV light. Silica gel (grade 9385, 230-400 mesh, 60 Å, Aldrich) was used for column chromatography. Elemental analysis was performed using an Exeter Analytical CE-440 elemental analyzer, model 440C / H / N / . Thermogravimetric analysis (TGA) was performed using a Q50 thermogravimetric analyzer (TA Instruments) at 10 K min under nitrogen atmosphere. -1 The scan rate was 100 s. An electrothermal MEL-TEMP capillary melting apparatus was used to measure the melting points. UV / VIS spectra were recorded using a Shimadzu UV-3600 spectrometer.
[0053] The contact angle was measured using a drop profile analysis system DSA25 manufactured by Kruss.
[0054] For FTIR and VSFG measurements, ITO was deposited on Si substrates and further functionalized with SAMs according to the methods described above.
[0055] FTIR spectra of the monolayers were recorded in transmission mode using an FTIR spectrometer Vertex80v (Bruker, Inc. Germany) equipped with a liquid nitrogen-cooled MCT narrow-band detector. The spectra were recorded at 4 cm -1The spectra were obtained from 512 interferogram scans with a resolution of 100 s, and the final spectrum was determined by averaging two spectra. A blank Si substrate with a 30 nm thick ITO layer was used as a reference sample. The sample chamber and spectrometer were evacuated during the measurements. The spectra were corrected by a polynomial function for background subtraction. No smoothing method was applied to the experimental data. The band parameters were determined by fitting the experimental contours to Gaussian Lorentzian shaped components using the software GRAMS / AI8.0 (Thermo Electron Corp).
[0056] The infrared spectrum of the V1036 baseline sample was recorded in transmission mode on an ALPHA FTIR spectrometer (Bruker, Inc, Germany) equipped with a room temperature detector DLATGS. The spectral resolution was 4 cm. -1 The spectrum was obtained from 124 interferogram scans. The sample was dispersed in a KBr pellet.
[0057] VSFG spectra were acquired using a commercially available VSFG system from Ekspla PL2143A20, which has been described in detail in a previous study. Briefly, a Nd:YAG laser produces pulses at 1064 nm with a pulse length of approximately 28 ps and a repetition rate of 20 kHz. A portion of the laser output is used to pump an optical parametric generator (Ekspla PG401VIR / DFG) to generate infrared pulses (ω IR ), which typically has energies of 60-200 μJ and is used to generate 1000 cm -1 ~4000cm -1 The second harmonic of the laser output (532 nm) is used as visible light (VIS) for sum frequency generation (ω SF). This sum frequency is generated when the infrared and visible pulses overlap in space and time at the sample surface. All spectra in this study were recorded using polarization combinations (s-SFG, s-VIS, p-IR). The intensity of the visible light was attenuated (~30 μJ) to avoid damage to the sample. The generated sum frequency light is filtered by a monochromator and detected by a photomultiplier tube (PMT).
[0058] The measured VSFG intensity is proportional to
number
[0059] Solid-state ionization potential (I p ) was measured in air by electron photoemission [14-16]. Samples for ionization potential measurements of V1036-based substrates were prepared by dissolving the materials in THF and applying them to an Al plate precoated with a methyl methacrylate-methacrylic acid copolymer adhesive layer of about 0.5 μm thickness. The layer thickness was about 0.5-1 μm. The PTAA layer on the ITO was formed by spin coating, similar to the process used for PSC formation. Through the above process, the SAM-HTM was formed.
[0060] Usually, photoelectron spectroscopy experiments are performed in vacuum, and high vacuum is one of the main requirements for these measurements. If the vacuum is not high enough, oxidation and gas adsorption on the sample surface will affect the measurement results. However, in the case of this study, the investigated organic materials are sufficiently stable against oxygen that measurements in air are possible. The samples were illuminated with monochromatic light from a quartz monochromator equipped with a deuterium lamp. The power of the incident light was (2–5)10 -8 A negative voltage of -300 V was applied to the sample substrate. 2A counter electrode with an illumination slit was placed at a distance of 8 mm from the sample surface. The counter electrode was connected to the input of a BK2-16 electrometer operated in open input mode for measuring the photocurrent. -15 ~10 -12 A strong photocurrent A flows through the circuit. The photocurrent I strongly depends on the incident light photon energy hν. I 0.5 In general, the dependence of the photocurrent on the incident quantum light energy is I 0.5 and hν. The linear part of this dependence is extrapolated to the hν axis, and the photon energy at the intersection is I p value was determined.
[0061] Laser structured indium tin oxide (ITO) glass substrate (25×25mm, 15Ωsq -1 The samples (Automatic Research GmbH, samples) were cleaned in an ultrasonic bath with 2% Mucassol solution, deionized water, acetone and isopropanol successively for 15 min. Afterwards, the samples were dried with a nitrogen gun and immediately prior to HTM deposition the substrates were treated with a UV ozone cleaner (FHR Anlagenbau) for 15 min.
[0062] All other procedures were carried out in a nitrogen-filled glove box.
[0063] SAMs of HTM were obtained by immersing UV-ozone treated ITO substrates in a 1 mM / L solution of the corresponding phosphonic acid molecules in isopropanol for 20 h, followed by annealing at 100 °C for 1 h, followed by washing with isopropanol and chlorobenzene. In addition to pure V1036 SAMs, mixtures of V1036 and n-butylphosphonic acid (C4) in different ratios were investigated to improve the monolayer quality and to investigate their impact on the solar cell device performance.
[0064] For PTAA control devices, PTAA (Sigma Aldrich) was dissolved in 2 mg mL of anhydrous toluene. -1The solution was spin coated at 4,000 rpm (5 sec acceleration) for 30 sec and annealed on a 100° C. hot plate for 10 min.
[0065] Triple cation Cs was synthesized according to a recently published method with slight modifications. 0.05 (MA 0.17 FA 0.83 ) 0.95 Pb(I 0.83 Br 0.17 )3 perovskite films were formed. First, PbBr2 and PbI2 were dissolved in DMF:DMSO (4:1 volume ratio) to a nominal concentration of 1.5 M by shaking overnight at 60 °C. Next, the stock solutions of PbBr2 and PbI2 were added to MABr and FAI powders, respectively, to obtain MAPbBr3 and FAPbI3 solutions with a final concentration of 1.24 M. The molar ratio of lead to the respective cations was 1.09:1.00 (9% excess lead) in both solutions. The MAPbBr3 and FAPbI3 solutions were then mixed in a 1:5 volume ratio. Finally, cesium cations were added with a 1.5 M CsI solution in DMSO in a 5:95 volume ratio. This final perovskite solution was slightly diluted by adding DMF:DMSO (4:1) in a 5:95 volume ratio for substrates with suboptimal wetting properties.
[0066] The precursor solution is deposited on top of the HTM layer by spin coating with the following program: 4,000 rpm (5 sec acceleration) for 35 sec (total time - 40 sec). After 25 sec, 500 μl of ethyl acetate is poured onto the spinning substrate. After the spin coating program, the perovskite-coated sample is annealed on a heating plate at 100 °C for 60 min.
[0067] On the perovskite, 23 nm of C60 and 8 nm of BCP were deposited by thermal evaporation (Mbraun ProVap 3G) at a base pressure below 1E-6 mbar with an evaporation rate of about 0.1–0.3 Å / s. Finally, 80–100 nm of Cu were evaporated at a rate of 0.3–1 Å / s to complete the device structure. The active area, defined by the overlap of the ITO and metal electrodes, is 0.16 cm2.2 It is.
[0068] Synthesis Route For V1036 [ka] 3,6-Dibromo-9-(2-bromoethyl)-9H-carbazole (1) The starting compound 3,6-dibromocarbazole (2 g, 6.15 mmol) was dissolved in 1,2-dibromoethane (40 mL) and then tetrabutylammonium bromide (0.198 g, 0.62 mmol) was added along with 50% aqueous KOH (1.72 mL, 30.77 mmol). The reaction mixture was stirred at 60 °C for 3 days with the addition of 0.198 g of tetrabutylammonium bromide and 1.72 ml of 50% aqueous KOH every 24 hours (TLC, acetone:n-hexane, 1:24, v:v). After completion of the reaction, extraction with dichloromethane was carried out. The organic layer was dried over anhydrous Na2SO4 and the solvent was removed under reduced pressure. The crude product was purified by column chromatography using acetone:n-hexane, 3:22, v:v as eluent to obtain 2·4 g (90%) of a white crystalline substance - compound 1 (Tm=153-155 °C).
[0069] Analysis:C 14 H 10 Calculated for NBr3, %: C 38.93; H 2.33; N 3.24; Found, %: C 38.78; H 2.42; N 3.11
[0070] 1 H NMR (400 MHz, CDCl3) δ 8,07 (d, J=1,8Hz, 2H);7,54 (dd, J=8,7, 1,9Hz, 2H), 7,25 (d, J=8,7Hz, 2H);4,59 (t, J=7,2Hz, 2H);3,62 (t, J=7,2Hz, 2H) 13 C NMR (100 MHz, CDCl3) δ 138.83;129.28;123.65;123.38;112.71;110.16;44.75;27.94.
[0071] [ka] Diethyl [2-(3,6-dibromo-9H-carbazol-9-yl)ethyl]phosphonate (2) Compound 1 (2.4 g, 5.55 mmol) was dissolved in triethyl phosphite (20 ml) and the reaction mixture was heated under reflux for 18 hours. After completion of the reaction (TLC, acetone:n-hexane, 2:3, vol:vol), the solvent was removed under reduced pressure. The crude product was purified by column chromatography using acetone:n-hexane, 7:18, vol:vol as the eluent to obtain a white crystalline substance - compound 2 (Tm=118-119°C).
[0072] Analysis: C 18 H 20 Calculated for NBr2O3P, %: C 44.20; H 4.12; N 2.86; Found, %: C 44.09; H 4.26; N 3.02.
[0073] 1 H NMR (400 MHz, CDCl3) δ 8.11 (d, J=1.8Hz, 2H);7.56 (dd, J=8.7, 1.9Hz, 2H);7.30 (d, J=8.7Hz, 2H);4.60 - 4.49 (m, 2H);4.04 (dq, J=14.2, 7.1Hz, 4H);2.28 - 2.16 (m, 2H);1.24 (t, J=7.1Hz, 6H).
[0074] 13 C NMR (100 MHz, CDCl3) δ 138.65;129.25;123.71;123.37;112.50;110.30;62.01;61.94;37.26;37.24;25.88;24.50;16.37;16.31.
[0075] [ka] Diethyl (2-{3,6-bis[bis(4-methoxyphenyl)amino]-9H-carbazol-9-yl}ethyl)phosphonate (3) A solution of compound 2 (1 g, 2.04 mmol) and 4,4'-dimethoxydiphenylamine (1.37 g, 6.13 mmol) in anhydrous toluene (50 mL) was flushed with argon for 20 min. Subsequently, palladium(II) acetate (0.137 g, 0.613 mmol), tri-tert-butylphosphonium-tetrafluoroborate (0.35 g, 1.23 mmol) and sodium-tert-butoxide (0.59 g, 6.13 mmol) were added and heated under reflux for 5 h under argon atmosphere. After completion of the reaction (TLC, acetone:n-hexane, 2:3, vol:vol), the reaction mixture was filtered through Celite. The solvent was removed under reduced pressure and the crude was purified by column chromatography using acetone:n-hexane, 7:18, vol:vol as the eluent to obtain 1 g (62.5%) of a green powder - compound 3.
[0076] Analysis:C 46 H 48 Calculated for N3O7P, %: C 70.30; H 6.16; N 5.35, Found, %: C 70.14; H 6.29; N 5.56.
[0077] 1 H NMR (400 MHz, DMSO-d6) δ 7.64 (d, J=2.2Hz, 2H), 7.46 (d, J=8.7Hz, 2H), 7.11 (dd, J=8.7, 2.2Hz, 2H), 6.86 - 6,74 (m, 16H), 4.56 - 4.44 (m, 2H), 3.92 (p, J=7.2Hz, 4H), 3.67 (s, 12H), 2.33 - 2.20 (m, 2H), 1.12 (t, J=7.0Hz, 6H).
[0078] 13 C NMR (101 MHz, DMSO) δ 154.16, 142.08, 140.25, 136.67, 124.39, 123.67, 122.90, 116.94, 114.60, 110.28, 61.20, 61.14, 55.15, 28.62, 16.13, 16.07.
[0079] [ka] (2-{3,6-bis[bis(4-methoxyphenyl)amino]-9H-carbazol-9-yl}ethyl)phosphonic acid (V1036) Compound 3 (0.4 g, 0.51 mmol) was dissolved in dry 1,4-dioxane (15 ml) under argon. Bromotrimethylsilane (0.67 ml, 5.08 mmol) was then added dropwise. The reaction was kept at 25° C. under argon atmosphere for 24 hours. The solvent was then removed under reduced pressure and the solid residue was dissolved in methanol (10 mL) and distilled water was added dropwise until the solution became opaque (10 mL) and then stirred for 15 hours. The product was filtered and washed with water to give 0.321 g (86%) of a green powder - compound V1036.
[0080] Analysis C 42 H 40 Calculated for N3O7P, %: C 69.13; H 5.52; N 5.76; Found, %: C 68.89; H 5.38; N 5.53.
[0081] 1 H NMR (400 MHz, DMSO-d6) δ 7.64 (s, 2H), 7.42 (d, J=8.8Hz, 2H), 7.11 (d, J=8.6Hz, 2H), 6.87 - 6.74 (m, 16H), 4.50 - 4.44 (m, 2H), 3.67 (s, 12H), 2.11 - 1.96 (m, 2H).
[0082] 13 C NMR (100 MHz, DMSO-d6) δ 154.16;142.09;140.22;136.66;124.60;123.66;122.88;117.15;114.63;110.01;66.36;55.16.
[0083] Synthetic route for the first adduct within the scope of the present invention: [ka] Tetraethyl-[(2,7-dibromo-9H-fluorene-9,9-diyl)di(ethane-2,1-diyl)]bis(phosphonate) (4) 2,7-Dibromofluorene (1 g, 3.08 mmol) was dissolved in 1,4-dioxane (30 mL) and diethyl-2-bromoethylphosphonate (1.55 mL, 9.25 mmol) was added dropwise, followed by three portions of sodium tert-butoxide (1.18 g, 12.34 mmol) every 10 min. The reaction mixture was stirred for 3 h, increasing the temperature by 20 °C every hour (30 °C to 70 °C). After completion of the reaction (TLC acetone:n-hexane, 7:18, vol:vol), extraction with diethyl ether was performed. The organic layer was dried over anhydrous Na2SO4 and the solvent was removed under reduced pressure. The crude was purified by column chromatography using acetone:n-hexane, 7:18, vol:vol as the eluent to give 1.25 g (62%) of a white crystalline substance - compound 4.
[0084] Analysis C 25 H 34 Calculated for Br2O6P2, %: C 46.03; H 5.25, Found, %: C 45.87; H 5.12.
[0085] 1 H NMR (400 MHz, CDCl3) δ 7.53 (s, 2H);7.52 (d, J=1.6Hz, 2H);7.46 (d, J=1.3Hz, 2H);4.08 - 3.87 (m, 8H);2.32 - 2.20 (m, 4H);1.26 (t, J=7.1Hz, 12H);1.02 - 0.88 (m, 4H).
[0086] 13 C NMR (175 MHz, CDCl3) δ 138.64;129.24;123.70;123.35;112.49;110.29;61.99;61.95;37.24;37.24;25.59;24.80;16.36;16.33.
[0087] [ka] Tetraethyl-[{2,7-bis[bis(4-methoxyphenyl)amino]-9H-fluorene-9,9-diyl}di(ethane-2,1-diyl)]bis(phosphonate) (5). A solution of compound 4 (1 g, 1.53 mmol) and 4,4'-dimethoxydiphenylamine (1.05 g, 4.59 mmol) in anhydrous toluene (50 mL) was flushed with argon for 20 min. Palladium(II) acetate (0.10 g, 0.46 mmol), tri-tert-butylphosphonium-tetrafluoroborate (0.28 g, 0.95 mmol) and sodium-tert-butoxide (0.44 g, 4.59 mmol) were then added and the solution was heated at reflux under argon for 6 h. After completion of the reaction (TLC, acetone:n-hexane, 2:3, vol:vol), the reaction mixture was filtered through Celite. The solvent was removed under reduced pressure and the crude product was purified by column chromatography using acetone:n-hexane, 7:18, vol:vol as the eluent to give 0.9 g (62%) of a yellow solid - compound 5.
[0088] Analysis C 53 H 62 N2O 10 Calculated P2, %: C 67.08; H 6.58; N 2.95, Detected, %: C 67.31; H 7.09; N 2.79.
[0089] 1 H NMR (700 MHz, CDCl3) δ 7.30 (dd, J=16.8, 9.4Hz, 2H);7.26 (s, 1H);7.24 - 6.71 (m, 19H);3.96 (p, J=7.2Hz, 8H);3.80 (s, J=14.1Hz, 12H);1.99 (dd, J=16.6, 7.2Hz, 4H);1.25 (t, J=7.1Hz, 12H);1.13 - 1.05 (m, 4H)
[0090] 13 C NMR (100 MHz, CDCl3) δ 155.85;146.59;141.60;141.04;127.85;126.38;122.47;120.62;119.17;114.76;61.44; 61.41;61.37;55.48;54.85;54.75;54.64;32.23;32.21;29.70;20.84;20.04;16.45;16.41
[0091] [ka] [{2,7-bis[bis(4-methoxyphenyl)amino]-9H-fluorene-9,9-diyl}di(ethane-2,1-diyl)]bis(phosphonic acid) (6) Compound 5 (0.88 g, 0.93 mmol) was dissolved in dry 1,4-dioxane (20 mL) under argon. Bromotrimethylsilane (1.96 mL, 14.88 mmol) was then added dropwise. The reaction was kept at 25° C. under argon atmosphere for 20 hours. The solvent was removed under reduced pressure and the solid residue was dissolved in methanol (10 ml) and distilled water was added dropwise until the solution became opaque (20 mL) and then stirred for 3 hours. The product was filtered and washed with water to give 0.230 g (80%) of a reddish powder - compound 6.
[0092] Analysis C 45 H 46 N2O 10 P2, % calculated: C 64.59; H 5.54; N 3.35, Detected, %: C 64.56; H 5.67; N 3.48
[0093] 1 H NMR (400 MHz, d8-THF) δ 7.34 (d, J=8.3Hz, 2H);7.19 (d, J=1.2Hz, 2H);7.02 (d, J=8.9Hz, 8H);6.80 (d, J=8.9Hz, 8H);6.74 (dd, J=8.2, 1.7Hz, 2H);3.71 (s, J=11.7Hz, 12H);2.09 (d, J=7.5Hz, 4H);0.99 - 0.85 (m, 4H)
[0094] 13 C NMR (100 MHz, d8-THF) δ 155.78;148.68;147.61;141.09;134.71;125.67;120.66;118.88;115.96;114.59;54.65, 31.70;28.37
[0095] Synthetic Route of a Second Further Compound V1193 Within the Scope of the Invention [ka] 9-(2-Bromoethyl)-3,6-dimethoxy-9H-carbazole (7) 3,6-Dimethoxycarbazole (0.534 g, 2.35 mmol) was dissolved in an aqueous solution (6.9 ml) of 1,2-dibromoethane (8 ml) and tetrabutylammonium bromide (0.08 g, 0.25 mmol) with 50% aqueous solution of KOH was added. The solution was stirred at 70 °C for 20 h until completion (TLC, acetone:n-hexane, 3:22, v:v). After completion of the reaction, extraction was carried out with ethyl acetate. The obtained organic layer was dried over anhydrous Na2SO4 and the solvent was distilled off under reduced pressure. The obtained raw product was purified by column chromatography using acetone:n-hexane, 1:49, v:v as the eluent. As a result, 0.352 g (60%) of a crystalline white material - compound 7 was obtained.
[0096] Analysis C 16 H16 Calculated for O2NBr, %: C 57.50; H 4.83; N 4.19; Found, %: C 57.39; H 4.86; N 4.15
[0097] 1 H NMR (400 MHz, CDCl3) δ 7.51 (d, J=2.5Hz, 2H), 7.29 (d, J=8.8Hz, 2H), 7.10 (dd, J=8.8, 2.5Hz, 2H), 4.62 (t, J=7.5Hz, 2H), 3.93 (s, 6H), 3.62 (t, J=7.5Hz, 2H)
[0098] 13 C NMR (101 MHz, CDCl3) δ 153.85, 135.65, 123.39, 115.30, 109.41, 103.45, 56.27, 45.07, 28.55
[0099] [ka] Diethyl [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonate (8) Compound 10 (0.316 g, 0.95 mmol) was dissolved in triethyl phosphite (2.7 ml) and heated under reflux for 18 h. After completion of the reaction (TLC, acetone:n-hexane, 1:4, vol:vol), the solvent was removed under reduced pressure. The crude product was purified by column chromatography using acetone:n-hexane, 1:1, v:v as eluent to obtain 0.353 g (95%) of a clear liquid - compound 8.
[0100] Analysis C 20 H 26 NO5P, % calculated: C 61.37; H 6.70; N 3.58; Detected, %: C 61.32; H 6.73; N 3.55.
[0101] 1 H NMR (400 MHz, CDCl3) δ 7.52 (d, J=2.5Hz, 2H), 7.30 (d, J=8.8Hz, 2H), 7.10 (dd, J=8.8, 2.5Hz, 2H), 4.60 - 4.49 (m, 2H), 4.09 - 4.03 (m, 4H), 3.93 (s, 6H), 2.29 - 2.15 (m, 2H), 1.28 (t, J=7.1Hz, 6H)
[0102] 13 C NMR (101 MHz, CDCl3) δ 153.67, 135.46, 123.37, 115.20, 109.49, 103.46, 62.02, 61.96, 56.28, 37.31, 26.15, 24.79, 16.56, 16.50
[0103] [ka] 2-(3,6-Dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (V1193) Compound 11 (0.335 g, 0.86 mmol) was dissolved in anhydrous 1,4-dioxane (25 ml) under argon atmosphere. Bromotrimethylsilane (1.12 ml) was then added dropwise. The reaction was kept at 25° C. under argon atmosphere for 24 hours. The solution was evaporated under reduced pressure and the solid residue was dissolved in methanol (15 ml) and distilled water (30 ml) was added until the solution became opaque and stirred for 15 hours. The product was filtered and washed with water to give 0.230 g (80%) of a beige solid -V1193.
[0104] Analysis C 16 H 18 NO5P, calculated %: C 57.32; H 5.41; N 4.18, detected %: C 57.19; H 5.53; N 4.11
[0105] 1 H NMR (400 MHz, MeOD) δ 7.57 (d, J=2.5Hz, 2H), 7.34 (d, J=8.8Hz, 2H), 7.05 (dd, J=8.8, 2.5Hz, 2H), 4.58 - 4.48 (m, 2H), 3.87 (s, 6H), 2.20 - 2.06 (m, 2H)
[0106] 13 C NMR (101 MHz, MeOD) δ 154.97, 136.71, 124.61, 116.03, 110.37, 104.29, 62.39, 56.46, 38.47
[0107] The synthetic route to a third further compound within the scope of the invention, V1194, is derived from the synthetic route to V1193 (see above) with the difference that 9H-carbazole is used instead of 3,6-dimethoxycarbazole.
[0108] A preferred example of the desired product can be formulated as follows: [ka] where HTF is a hole conducting fragment, L is a connecting fragment, A is an anchor group, and n=1-2. A- Phosphonic acid, phosphoric acid, sulfuric acid, sulfonic acid, carboxylic acid, siloxane, etc. [ka] R'- hydrogen, C1-C9 alkyl group, L- C1-C9 alkylene, C4-C 20 Arylene, C4~C 20 Heteroarylene, C4-C 20 Alkyl arylene, C4-C 20 heteroalkylarylene, where the heteroatoms are selected from O, N, S, Se, Si, and alkylene, arylene, heteroarylene, alkylarylene, heteroalkylarylene, when they consist of 3 or more carbon atoms, may be linear, branched or cyclic; for example: [ka] HTF: [ka] R: hydrogen [ka] X - halogen (F, Cl, Br, I) R': Hydrogen, alkyl (C1-C12) R'': Hydrogen, alkyl, alkoxy (-CH3;-OCH3)
[0109] SAMs of V1036 and mixed V1036 and n-butylphosphonic acid (C4) were formed by immersing UV-ozone-treated ITO substrates in a 1 mM solution of the phosphonic acid molecules in isopropanol for 20 h, followed by annealing at 100 °C for 1 h and rinsing with isopropanol and chlorobenzene. To eliminate the possible adverse effects of atmospheric oxygen, all procedures were carried out in a nitrogen-filled glove box.
[0110] V1193 in solution was spun onto an ITO substrate and then annealed at 100° C. for 10 minutes, with optional rinsing. V1193 shows improved properties over V1036, as can be seen in FIG.
[0111] In Fig. 10, the parameters of efficiency in % (▲, values for the outer left ordinate, with error bars), quasi-Fermi level splitting (QFLS) in eV (●, values for the inner left ordinate), and open circuit voltage VOC in Volts (★, values for the inner left ordinate, with error bars) are shown for the “triple cation” perovskite absorber (Cs5(MA 17 FA 83 Pb(I 83 Br 17 )3) 95The photoluminescence lifetimes in μs (bars, values against the right ordinate) are plotted for the various HTM-SAMs, V1036, V1193, V1194 and also compared with PTAA. The data were obtained from a compositional analysis. The measured parameters were measured at a solar equivalent irradiance (AM1.5g standard). The bars indicate the maximum measured photoluminescence lifetime. The area between the solid curve lines indicates the maximum and minimum measured QFLS (from 3 V1036, 8 V1193 and 9 V1194 samples). The error bars for the open circuit voltage Voc and efficiency indicate the standard deviation of the measurements for 38 V1036, 56 PTAA, 42 V1193 and 40 V1194 cells. A clear correlation can be seen between efficiency, Voc, photoluminescence (PL) lifetime and QFLS. The V1193 and V1194 SAMs outperformed PTAA, the current standard for high-efficiency inverted perovskite solar cells, in PL lifetime, QFLS, and device performance. The V1036 values are close to those of PTAA. The dotted line shows the PL lifetime on glass for reference. Although not included in the figures, the advantageous HTM-SAMs of the present invention are significantly cheaper than PTAA.
[0112] Here we define for the first time hole-conducting SAMs that can be used in pin-architecture PSC devices with overall efficiencies of about 18% or higher. Furthermore, due to their (covalent) bonding to the substrate layer, the layers formed by these SAMs are resistant to perovskite processing and can potentially conformally cover any textured oxide surface. Thus, these molecules are ideally suited for the direct integration of monolithic perovskite / silicon solar cells on structured silicon wafers.
[0113] Furthermore, based on the abovementioned fragments, the new HTM can be extended to serve as a model system for substrate-based perovskite nucleation and passivation control.
[0114] The research in this project has been funded by the Horizon 2020 EU funding programme under Grant Agreement No. 763977 of the PerTPV project.
[0115] List of Abbreviations
[0116] [Table 4]
Claims
1. 1. A method for forming a self-assembled monolayer on a TCO substrate for use in an inverted architecture perovskite solar cell, the method comprising the steps of: Providing a substrate coated with an oxide layer - coating the substrate with a compound of the molecule of formula (I) or a mixture comprising a compound of the molecule of formula (I) and a filler molecule FM, immersing the substrate in a solution comprising a solvent and the compound or mixture, or spinning the compound or mixture in solution onto the substrate; The formula (I) is: 【Chemistry 1】 In formula (I), L is a linking fragment and consists of C 2 -C 4 alkylene or one of the following formulae (l-1) and (l-2), where the dotted lines represent the bonds by which L is connected to HTF and A: 【Chemistry 2】 A is an anchor group selected from phosphonic acid, phosphoric acid, sulfuric acid, sulfonic acid, and carboxylic acid; n is 1 or 2, and HTF is a hole conducting fragment of formula (IV) or (V) 【Chemistry 3】 【Chemistry 4】 In formulas (IV) and (V), R is independently selected from the group consisting of H; C 1 -C 10 alkyl; C 2 -C 10 alkenyl; C 3 -C 20 cycloalkyl; C 3 -C 8 heterocycloalkyl, alkoxy, aryloxy, alkylthio, arylthio, amino, amide, ester, carboxylic acid, dialkoxydiphenylamine, carbamate, urea, ketone, aldehyde, cyano, nitro, halogen; (cycloalkyl)alkyl; and (heterocycloalkyl)alkyl; and the dotted line represents the bond connecting HTF to L; The mixture comprises: 【Chemistry 5】 is given by In formula (I), L, HTF, A and n are as defined above; FM is at least one molecule formed by an anchor group selected from phosphonic acid, phosphoric acid, sulfuric acid, sulfonic acid, carboxylic acid and siloxane, an alkyl chain having N carbon atoms, where N ranges from 1 to 18, and any one of the functional groups methyl, halogen, amino, ammonium and sulfur; x ranges from 0.02 to 1 and y is (1-x), with the proviso that x is not 1; The method comprising:
2. The method of claim 1 , wherein the compound or mixture is spin-coated, the spin-coating being performed by spin-coating.
3. 3. The method according to claim 1 or 2, - subsequently thermally annealing and / or cleaning the substrate; The method.
4. R is independently selected from hydrogen or any of the following formulae (r-7) to (r-11): 【Chemistry 6】 The dotted line represents the bond connecting R to HTF; R″ is hydrogen, alkyl, alkoxy (—CH 3 ;-OCH 3 The method according to any one of claims 1 to 3, wherein
5. The method according to any one of claims 1 to 4, wherein the hole conducting fragment HTF is of formula (IV): 【Chemistry 7】
6. A is a phosphonic acid group and L is C 2 2. The method of claim 1, wherein R is an alkylene and R is a methoxy group.
7. A is a phosphonic acid group and L is C 2 2. The method of claim 1 , wherein R is alkylene and R is hydrogen.
Citation Information
Patent Citations
P-doped conjugated low-molecular electrolyte, and organic electronic device arranged by use thereof
JP2016129224A
Method and device for manufacturing semiconductor element
JP2017059643A
Printable thin-film transistors with high dielectric constant gate insulators and methods for producing same
US20100051917A1
Film-forming composition containing crosslinkable reactive silicone
WO2016080226A1